Analysis and international comparison of labour productivity of Hungarian Dairy Farms - Geszti, Szilárd; Borbély, Csaba (Acta Agraria Kaposváriensis, 2005)
Resources needed in production are limitedly available, therefore a strong competition exists to own and use them. With joining the European Union, this pressure became stronger among the producers due to a higher number of the competitors. In this situation, the significance of international comparisons is higher, because the actors of the market can estimate their future situation only this way in the enlarged EU. The network of European Dairy Farmers (EDF) gives the opportunity for this; where in 2003, dairy farms of already 19 countries were compared by using economic indicators. The basis of the partial analysis is the survey on the productivity of labour as production factor. A high share of the costs comes from applying labour in production. Its role and used amount will however change, therefore it is necessary to analyse the use of labour in order to improve the economic results of dairy farming. It is commonly known that the productivity parameters of the Hungarian dairy farms are lower than those of western European farms (Borbély et al., 2000); however the question arises at what level the labour is used in Hungarian dairy farms. From all mentioned previously, the current study deals with the labour productivity of Hungarian dairy farms and revealing the reasons and causes, by comparing the Hungarian productivity with the averages of the EDF and western German dairy farms.
Keywords: production factor; labour productivity; EDF; international analysis